Positive UX and Active Use of ICT Devices among the Elderly - Ayako Hashizume; Masaaki Kurosu (International Journal of Informatics and Communication Technology (IJ-ICT), 2013)
People have started to use ICT(Information and Communication Technology) devices to acieve various goals in many situations.  But a gap still exsists between high end users and low end users that is related to their demographic group. One of the important traits is the generation or the age group.  Authors conducted field research by the contextual inquiry method and analyzed the data by applying M-GTA, then summarized the information into a category relationship diagram. In this diagram,factors such as the motivation for using ICTs, active involvement in the communication and ICT literacy were regarded as three major components.DOI: http://dx.doi.org/10.11591/ij-ict.v2i1.1506